Analisis Kepuasan Masyarakat Terhadap Pelayanan E-KTP Berdasarkan IKM di Kantor Kecamatan Kabupaten Madiun - Dinata, Nadlirotul Azizah; Utami, Dian Arlupi (Universitas Negeri Surabaya, 2023)
In its implementation, the government always tries to provide satisfaction for the community by always improving the quality of its services, but there are still many complaints given to the government for maladministration that occurs in Indonesia. In dealing with this, the government is still trying to improve the services they have in each service delivery unit, one of which is by conducting a community satisfaction survey. This study uses Permenpan RB Number 14 of 2017 which includes 9 indicators, namely requirements, procedures, time, costs, products, employee competence, employee attitudes, handling complaints and infrastructure as research guidelines. Descriptive using a Quantitative approach is the method that will be used in this study. In accordance with the SKM Guidelines, the results of the data tabulation calculation obtained that the E-KTP service in the Geger sub-district obtained a Community Satisfaction Index figure of 80.74 IKM, which at this figure explains that the E-KTP service in Geger District is in the